IMPLEMENTASI ALAT PEMADAM API RINGAN (APAR) SEBAGAI UPAYA PENCEGAHAN DINI BAHAYA KEBAKARAN DI PT CONTEMPORARY AMPEREX TECHNOLOGY LIMITED ENERGY ENGINEERING (PT CCIEE) - Iin Ira Kartika; Chaerani Triyuliana; Wieke Widhiantika; Wendi Dermawan; Jumaedi Jumaedi; Devi Fitriyastanti; Yasin Azhari; Najwa Khoirotun Nisa (Jurnal Kesehatan dan Kedokteran, 2025)
Fire is one of the major risks in construction and energy industries that can cause material losses, operational disruptions, and threaten workers’ safety. One of the early fire prevention efforts is the implementation of portable fire extinguishers (APAR) as an active fire protection system in the workplace. Objective: This study aims to analyze the implementation of portable fire extinguishers as an early fire prevention effort at PT Contemporary Amperex Technology Limited Energy Engineering (PT CCIEE). Method: This research employed a descriptive qualitative method with a field study approach. Data were collected through observation, documentation, and literature review, while data analysis was conducted through data reduction, data presentation, and conclusion drawing using descriptive qualitative analysis. Findings: The results showed that PT CCIEE had implemented portable fire extinguishers as part of an active fire protection system in high-risk work areas, such as welding areas, electrical panels, and heavy equipment zones. However, several issues were still identified, including nonfunctional extinguishers, improper extinguisher placement, and the need for improved worker training on extinguisher usage. Implication: This study indicates that the effectiveness of portable fire extinguishers is not only determined by equipment availability, but also by proper placement, regular inspection, and workers’ preparedness in using fire extinguishers. Originality: The originality of this study lies in its focus on the implementation of portable fire extinguishers within construction and energy industry projects in Indonesia, which remains limited in previous studies.